2019
DOI: 10.1063/1.5128526
|View full text |Cite
|
Sign up to set email alerts
|

Production of O− and O2− beams with the negative ion source at Institute of Modern Physics

Abstract: A negative oxygen ion source is under development to produce O− and O2− beams used for a secondary ion mass spectrometer at Institute of Modern Physics (IMP), and both filament and radio frequency (RF) schemes are tested. The filament driven ion source, which was initially designed for H− production, has a 10-pole multicusp plasma chamber, two sets of virtual magnetic filters, and a 3-electrode extraction system. The RF scheme, which is improved by changing a RF back plate from the filament ion source, has an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Initially, we tried a filament-driven ion source to extract negative oxygen ion beams, with oxygen and carbon dioxide gases injected [22]. However, after the preliminary operation, we found that the corrosive nature of such plasmas would cause hot-cathode failure.…”
Section: Rf Ion Source Design With An External Antennamentioning
confidence: 99%
“…Initially, we tried a filament-driven ion source to extract negative oxygen ion beams, with oxygen and carbon dioxide gases injected [22]. However, after the preliminary operation, we found that the corrosive nature of such plasmas would cause hot-cathode failure.…”
Section: Rf Ion Source Design With An External Antennamentioning
confidence: 99%